Dedang Songke Sebagai Home Based Production - Dugis, Desideria Alfani; Suwena, I Wayan; ., Aliffiati (Humanis; Vol 24 No 1 (2020)DO - 10.24843/JH.2020.v24.i01.p11, 2020)
Dedang songke or the activity of weaving traditional cloth (songke) is a tradition that is still widely practiced by housewives as the ancestral heritage of Manggarai Community, especially in the Orchard of Ringkas. The objectives of this study are (1) to find out the reasons why women in Ringkas Orchard made dedang songke as home based production (2) to find out the implications of dedang songke as home based production for the lives of the weavers, their families, and the people of Ringkas Orchard. This study uses the need achievement theory and the rational choice theory. While the concept used in this study are dedang songke, handicraft industry, and home based production. In this study, the research method used was qualitative with two data sources namely primary data and secondary data, through observation and interview for collecting the data. The results found from the research show that the background of the housewives in Ringkas Orchard works as weavers because of internal and external factors. Internal factors include: the desire to help husband to fulfill family needs, the desire to get recognition and the desire to continue their ancestral’s heritage. While external factors include: insufficient employment, inadequate farming/gardening production, and educational factor. The struggle of women in dedang songke handicraft industry as home based production has implications for the individual weavers, their families, and communities.